ANIMASI INTERAKTIF MENGENAL ATURAN LALU LINTAS UNTUK SISWA SEKOLAH DASAR - Ramadhani; Feri Susilawati; Devi Mulia Sari; Ichsan (Politeknik Aceh, 2022)
Traffic signs as a symbol of road discipline are usually found on every street corner which functions for order and convenience for road users. Traffic signs are made to be obeyed by road users, but most elementary school students do not understand the meaning of each symbol of the existing traffic signs. So students need to be given learning about the introduction of existing traffic signs. To make students enthusiastic and happy in learning to recognize the rules of traffic signs, an interactive animation application was created as a learning medium which contains the distribution of traffic signs, the meaning of the symbol for each sign, an animated video of the application of road signs, as well as practice questions with the support of interactive buttons, interesting pictures and audio to increase students' learning absorption of the content of learning material